Diseño de un sistema de control de inventario para la distribuidora “Agua Santa”. - Tercero Tercero, Elva Karina (2019)
The purpose of this research is to design an inventory control system that brings together technical procedures in handling to achieve optimum levels of efficiency in the development of merchandise control processes in the "Agua Santa" distributor, in the Salcedo canton, province of Cotopaxi was based on the countryside and bibliographic analysis through research instruments such as the interview and observation sheet, allowing us to identify the current inventory process and the possible problems and weaknesses, caused by empirical management, established the correct way of taking a physical inventory to determine differences. The documents were designed to support their accounting record, and policies were established that allowed adequate control in the achievement of the processes. It was concluded that the company will have an inventory control system that allows for an updated and timely handling of its merchandise, so that the information that is transmitted was truthful and timely, in addition to the fact that its processes were established in written form that allowed its knowledge to personal. Management was proposed to take into account the use of the proposed model to achieve optimum levels of efficiency in the development of production processes